Level of Acceptability of Bilimbi Jam (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Bilimbi is a commonly cultivated tree species of the Old-World tropics that was introduced in the 1790s to the Neotropics, where it has been since naturalized. This species is also cultivated in Western Africa (Burkill, 1985). It is listed in the Global Compendium of Weeds as a “naturalized, weed” and known to be invasive in the Old-World tropics. An experimental research design was used here. A simple random sampling technique was used in this study. A survey questionnaire was used as the instrument in this study. From all variables, we calculated the total of their answer, and we divided60 for all data of the respondents. Lastly, we multiplied it by100. Bilimbi fruit is not only ingested in the dish; it is the God for the body and health, and it can help people with an ulcer. We made this bilimbi jam because some children do not eat bilimbi due to its sour taste. Children also do not know the nutrients that they can get from this fruit. We hope that future researchers will find this work helpful. We are hoping that they will appreciate and love our product.
Keywords: bilimbi jam